Hybrid inductor for improving gain attenuation characteristics of a Pi filter circuit. (December 2020) - Tanaka, Masato; Shimura, Kazuhiro; Sato, Mitsuhide; Mizuno, Tsutomu; Matsuoka, Takashi
Abstract: A filter circuit is required to suppress noise and have high gain attenuation characteristics in a wide band. Gain attenuation decreases because the relative permeability of an inductor core employed in a filter circuit drops sharply as drive frequency increases. Thus, by combining a core with a magnetic composite material with excellent frequency characteristics, we suppressed inductance reduction over a wide frequency range. As a result, the inductance of a hybrid inductor increased by 17.8% and 116% at 1 and 80 MHz, respectively, compared with that of a conventional inductor. When we applied a hybrid inductor to a Pi filter circuit, it was attenuated by 6.5 and 5.0 dB at 100 and 80 MHz, respectively, compared with a conventional inductor.